Chinese Sources in Thai Scholarly Historical Works - Tungkeunkunt, Kornphanat; Han, Changqing; Zhao, Wenjie (Parichart Journal, 2024)
Scholarly works on modern history of Thailand have long emphasized a variety of sources, as different materials reflect different perspectives and narratives. Despite a great number of primary sources from foreign countries used in Thai scholarship, little attention has been paid to Chinese materials. This is unfortunate as China has played a crucial role in Siamese/Thai history. Therefore, this article attempts to explore a variety of Chinese sources in the historical study of Siam/Thailand. It demonstrates how the use of Chinese materials can provide valuable insights into various aspects of Siamese/Thai society, including the relationships between Thailand, China and other states. To classify Chinese source materials, this paper is divided into three sections, i.e., Chinese chronicles, Chinese archives, and Chinese-language miscellany. It will examine how Thai scholarly historical works have interpreted the Chinese materials from past to present.